2016
DOI: 10.1016/j.ijid.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the immunogenicity and safety of pentavalent vaccine Quinvaxem in a compact prefilled auto-disabled (cPAD) injection system versus single-dose vials in healthy infants: a phase 3, open-label, randomized, parallel-group, non-inferiority study

Abstract: Quinvaxem in cPAD was non-inferior to single-dose vial with respect to seroprotection/seroconversion rates for all antibodies. Both presentations were well-tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The ultimate goal of vaccination for public health is to prevent bacterial and viral infections. The Pentavalent vaccine is expected to reduce the procedural steps, vaccination process time, storage needs, and to minimize vaccine wastage as compared to conventional administration with a syringe (2). In the present study, the immunogenicity of the Pentavalent vaccine was evaluated in addition to the comparison of antibody titers before and after three doses and evaluating its complications and side effects in vaccinated infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ultimate goal of vaccination for public health is to prevent bacterial and viral infections. The Pentavalent vaccine is expected to reduce the procedural steps, vaccination process time, storage needs, and to minimize vaccine wastage as compared to conventional administration with a syringe (2). In the present study, the immunogenicity of the Pentavalent vaccine was evaluated in addition to the comparison of antibody titers before and after three doses and evaluating its complications and side effects in vaccinated infants.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization, as a cost-effective and life-saving intervention, is a fundamental component of public health policies for controlling infectious diseases (1,2). Nowadays, multivalent vaccines like the tetravalent (DTP-Hib or DTP-HepB) or the Pentavalent (DTP-HepB-Hib) combination vaccines have been added to the immunization program in many countries (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other researchers have also investigated the safety of pentavalent vaccines in diverse settings. Bavdekar et al [30], Angela et al [31], Dodoo et al [32], Sharma et al [33], Asturias et al [34], Maria et al [35], and Manoochehr et al [36] conducted studies across various populations. These studies predominantly identified non-serious AEFIs, which typically resolved with or without medication.…”
Section: Introductionmentioning
confidence: 99%